THE IMPLEMENTATION OF SCIENTIFIC APPROACH THROUGH DIGITAL STORYTELLING IN TEACHING READING NARRATIVE TEXT - Ainun Nurbaeti; Yanuarti Apsari (IKIP Siliwangi, 2022)
This study is aimed at describing the implementation of scientific appproach through digital storytelling in teaching reading narrative text. The participants of the study were the tenth grade students in SMA Pasundan Cikalong. Furthermore, this study employed case study as research design and conducted the classroom observation sheet to find out how the teacher implemented scientific approach in teaching reading narrative text. The finding of the study showed that the teacher implemented of scientific approach in teaching reading through several stages such as observing, questioning, experimenting, associating and communicating. In addition, during learning reading narrative text through digital storytelling, students become more engaged in the classroom as a result of their enjoyment. It may be stated that using a scientific approach through digital storytelling made it easier for students to understand the narrative text. Finally, the writer recommends that an English instructor use a scientific approach to teaching narrative text reading during the learning process. Keywords: Scientific Approach, Digital Storytelling, Teaching Reading, Narrative Text